The Impact of Price Reductions on Individuals' Choice of Healthy Meals Away from Home - Jonas Nordström; Linda Thunström (Lund University, School of Economics and Management, Department of Economics, 2013)
Food high in energy but low in nutritional value is an important contributor to several serious illnesses, and one type of food that is particularly high in energy but low in nutrition is food consumed away from home. In this paper, we examine the demand and willingness to pay for healthy, Keyhole-labelled meals. A Keyhole-labelled meal is particularly low in calories, fat, sugar and salt, but particularly high in fibre. The results suggest that to get the majority of individuals to choose the healthy option regularly it would be necessary to alter the relative price between healthy and less healthy meals. Generally groups of individuals with a poor nutritional intake require a larger compensation (subsidy) before they choose the healthy alternative. About one third of respondents would choose the healthy option regularly if the prices for a healthy and less healthy meal were the same. In particular groups of individuals who already have a relatively good nutritional intake would select the healthy option. Groups with a generally poor nutritional intake (men and individuals with lower education and lower income) would gain health benefits from a subsidy of Keyhole-labelled meals.
Keywords: D12; H20; H31; I18; 330; subsidy; food demand; food away from home; healthy; restaurant